2015
DOI: 10.1039/c4dt02981j
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the design of dual-modal MR/fluorescent probes to sense zinc ions

Abstract: A series of gadolinium complexes were synthesised in order to test the design of dual-modal probes that display a change in fluorescence or relaxivity response upon binding of zinc. A dansyl-DO3ATA gadolinium complex [GdL1] displayed an increase and a slight blue-shift in fluorescence in the presence of zinc; however, a decrease in relaxation rate was observed. Consequently, the ability of the well-known zinc chelator, BPEN, was assessed for relaxivity response when conjugated to the gadolinium chelate. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The latter drawback can be circumvented by choosing the absorption and emission wavelength close to the biological window [16]. Different optical probes have already been coupled to DTPA or DOTA, such as luminescent polymers in lipophilic aggregates [17], luminescent metal complexes [18][19][20][21][22][23][24][25][26][27], dendrimers [28], and organic dyes such as quinolone [29], rhodamine [30,31], fluoresceine [32], and naphalimide [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The latter drawback can be circumvented by choosing the absorption and emission wavelength close to the biological window [16]. Different optical probes have already been coupled to DTPA or DOTA, such as luminescent polymers in lipophilic aggregates [17], luminescent metal complexes [18][19][20][21][22][23][24][25][26][27], dendrimers [28], and organic dyes such as quinolone [29], rhodamine [30,31], fluoresceine [32], and naphalimide [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of dansyl based probes for the detection of metal ion have been reported, mainly based on the electron transfer effect (ET) between metal ion and the excited dansyl uorophore in the coordination state. [17][18][19][20][21] Obviously, this strategy isn't suit for the design of probes for biological molecules such as Cys. To the best of our knowledge, dansyl based uorescent probes for Cys are rare.…”
mentioning
confidence: 99%
“…It was found that the emission intensity of 3 increases under more acidic conditions. As the pH is lowered the spirolactam ring of the molecule opens, yielding a greater fluorescence (Figure S23), as observed in other rhodamine conjugates . Correspondingly, the quantum yield of 3 at pH 7.5 was found to be 16.6 % while at pH 4.3 it was 25.9 %.…”
Section: Methodsmentioning
confidence: 54%
“…Correspondingly, the quantum yield of 3 at pH 7.5 was found to be 16.6 % while at pH 4.3 it was 25.9 %. A titration curve was produced by plotting the emission maximum of 3 at 582 nm as a function of pH, yielding a p K a value of 4.59, which is comparable to that of rhodamine DOTA conjugates (DOTA=1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid) with a p K a of 5.5 . However, in the case of AuNP.3 the opposite effect is observed: a higher fluorescence emission observed at high pH rather than low pH, corresponding to a quantum yield of 0.8 % at pH 8.1, and 0.2 % at pH 5.1.…”
Section: Methodsmentioning
confidence: 99%